Pedagogical reforms within a centralised-decentralised system: A Singapore's perspective to diffuse 21st century learning innovations. Issue 7 (12th September 2016) - Toh, Yancy; Hung, Wei Loong David; Chua, Paul Meng-Huat; He, Sujin; Jamaludin, Azilawati
Abstract : Purpose: The purpose of this paper is to illustrate the dialectical interplay between centralisation and decentralisation forces so as to understand how schools leverage on its autonomous pedagogical space, influence the diffusion of innovations in the educational landscape of Singapore and how a centralised-decentralised system supports (or impedes) pedagogical reform for twenty-first century learning. Design/methodology/approach: The paper first outlines the evolutionary stance of Singapore's decentralisation from its past to present trajectories, thus providing a broader social-historical interpretation to its tight-loose-tight coupling of the education system; followed by situating the context of reform within the national narrative of Ministry of Education's (MOE) twenty-first century competencies framework. The authors examine how school autonomy should be accompanied by systemic enabling mechanisms, through two case illustrations of whole-school reforms. Findings: There are four carryover effects that the authors have observed: structural, socio-cultural, economic and epistemic. Middle managers from the two schools act as a pedagogical, socio-technological and financial broker outside the formal collaborative structures organised by the MOE. Such a "middle-out" approach, complemented by centralised mechanisms for "coeval sensing mechanism", has resulted in boundary-spanning linkages and multiplier effects in terms of knowledge spillovers. Research limitations/implications: Socio-cultural context matters; and what constitutes as co-learning between policymakers and practitioners in Singapore may be construed as policing that stifles innovations in other contexts. Originality/value: In addition to the conceptualisation of how school autonomy may lead to school-based innovations, the paper provided some preliminary empirical evidence of how the co-production of knowledge has been engendered within, across and beyond individual Singapore schools through the mechanism of innovation diffusion. The unit of analysis is innovation ecosystem.